Seed metrics for genetic and shape determinations in African yam bean [Fabaceae] (Sphenostylis stenocarpa Hochst. Ex. A. Rich.) harms - Adewale, B.D.; Kehinde, O.B.; Aremu, C.O.; Popoola, J.O.; Dumet, D.J. (2010)
The metric measures on seeds, their correlation and relationship are important for systematic breeding for seed yield and shape determination. Variations among eighty genotypes of African yam bean (AYB) for six metric seed characters (seed length, width and thickness and their ratios) were evaluated in this study. Paired comparison among the six characters revealed very high significance (P < 0.001), approving the six traits as unique parameters for evaluating AYB. They equally exhibited high and substantial genetic variance: the genotypic proportion of the total variation ranged between 90 and 97%, broad sense heritability (81 - 94%) and genetic advances (14 - 31%). Seed length and width had the highest joint inheritance of 99.04%, the least, 4.32% was between width and WT as depicted by coheritability. Positive and significant (P < 0.05) phenotypic and/or genotypic correlation existed between seed width and thickness, the three ratios and seed length with the ratios except WT. Non-significant negative correlation existed between seed thickness with LT and WT. There were very reliable and highly significant linear relationships between the seed traits except for length and width whose relationship was non-linear. Breeding concentration on any of these traits may simultaneously influence the others. The seed shape indices were the metric ratios and the flatness index; they described the common shapes of AYB seeds as: round/spherical, oval/ellipsoidal, oblong and rhomboid